Art Music: John Singer Sargent as Listener, Practitioner, Performer and Patron. Issue 1 (2nd January 2018) - Langley, Leanne
Abstract : Music was more than a side interest or social activity in the life and work of John Singer Sargent. Studying, playing and listening to it for most of his career equipped him with perceptual and tactile skills that appear to have influenced his artistic technique. Further, his move to London in 1886 opened fresh opportunities for musical engagement, underrated in art historical narratives heretofore. By examining aspects of Sargent's music development as listener, practitioner, performer and patron, alike through specific pieces he knew and design parallels in his paintings, this article shows how integral music was to Sargent's individuality.